Production of 7-methylxanthine from Theobromine by Metabolically Engineered E. coli - Algharrawi, Khalid Hussein Rheima; Subramanian, Mani (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
In this work, a novel biocatalytic process for the production of 7-methylxanthines from theobromine, an economic feedstock has been developed. Bench scale production of 7-methlxanthine has been demonstrated. The biocatalytic process used in this work operates at 30 OC and atmospheric pressure, and is environmentally friendly. The biocatalyst was E. coli BL21(DE3) engineered with ndmB/D genes combinations. These modifications enabled specific N7- demethylation of theobromine to 7-methylxanthine. This production process consists of uniform fermentation conditions with a specific metabolically engineered strain, uniform induction of specific enzymes for 7-methylxanthine production, uniform recovery and preparation of biocatalyst for reaction and uniform recovery of pure 7-methylxanthine.   Many E. coli BL21(DE3) strains metabolically engineered with single and/or multiple ndmB/D genes were tested for catalytic activity, and the best strains which had the higher activity were chosen to carry out the N-demethylation reaction of theobromine. Strain pBD2dDB had the highest activity for the production of 7-methylxanthine from theobromine. That strain was used to find the optimum amount of cells required to achieve complete conversion of theobromine to 7-methylxanthine within two hours. It was found that the optimum concentration of pBD2dDB strain to achieve 100% conversion of 0.5 mM theobromine to 7-methylxanthine was 5 mg/mL. The cell growth of pBD2dDB strain was studied using two different growth media, (Luria-Bertani Broth and Super Broth). Super broth was found to be the best medium to produce the highest amount of cell paste (1.5 g). Subsequently, the process was scaled up in which 2 L reaction volume was used to produce 7-methylxanthine (100% conversion) from 0.5 mM theobromine catalyzed by pBD2dDB strain. The reactions was carried out at 30 oC and 250 rpm shaker speed, and the reaction medium was 50 mM potassium phosphate buffer (pH=7). 7-methylxanthines was separated by preparative chromatography with high recovery, and the product solution was collected, purified by drying at 120-140 oC for 4 hours and, recovered (127 mg). Purity of the isolated 7-methylxanthine was comparable to authentic standards with no contaminant peaks, as observed by HPLC, LC-MS, and NMR.